Subjective Family Socioeconomic Status and Peer Relationships: Mediating Roles of Self-Esteem and Perceived Stress - Bai, Xia; Jiang, Liping; Zhang, Qi; Wu, Ting; Wang, Song; Zeng, Xiaoying; Li, Yanjia; Zhang, Li; Li, Jingguang; Zhao, Yajun; Dai, Jing (Frontiers in Psychiatry, 2021)
Abstract This study explored the relationships between subjective family socioeconomic status (FSES), self-esteem, perceived stress, and perceived peer relationships among Chinese adolescents. A total of 1,353 adolescents (age range: 15−19 years) were asked to complete a questionnaire. Mediation analysis revealed that subjective FSES influenced perceived peer relationships in three ways: first, through the mediating effect of perceived stress; second, through the mediating effect of self-esteem; and third, through the serial mediating effects of perceived stress and self-esteem. The results remained significant after controlling for parental education. In addition, a contrast analysis showed no significant differences in the mediating effects of self-esteem and perceived stress. Thus, we suggest that steps should be taken to improve adolescents’ self-esteem and reduce their stress through training interventions and preventive measures, to help them improve their perceived peer relationships and reduce adverse effects associated with low subjective FSES.